(untitled) (International Journal of Physiology, 2019)
Background Haemostasis is the stoppage of bleeding. Bleeding time (BT) and Clotting time (CT) assess the integrity of haemostatic mechanisms. Assessment of Hematological parameters like bleeding time, clotting time and blood grouping are a very important before initiating any surgical procedure. Blood group has clinical importance in transfusion medicine and medico legal cases. Some studies have showed epistaxis and thrombosis found in O blood group individuals. Earlier studies showed the conflicting results regarding association of blood group with clotting time and bleeding time. Objectives The aim of the study was to assess the distribution of ABO blood groups in males and females with age group of 17-21yrs and determination of BT and CT among males & females. To analyze the relationship between the blood groups, BT and CT. Method The study was conducted in Department of Physiology, Mamata Medical College. The study included 205 healthy volunteers of age group between 18-21years. Blood grouping, bleeding time and clotting time were determined. Statistical analysis done by un paired t test for calculating gender wise CT and BT and ANOVA and Post Hoc test for assessing relationship between BT, CT and blood groups. Results Our study results showed that blood group O was predominant in both males and females. Clotting time and bleeding time is statistically higher in females compared to males. Results showed clotting time is statistically significant (0.011) only between group A & group O, with higher value in group O but not the bleeding time. Conclusion Blood group O was the most common group. BT and CT were higher in females than males. May be due to high estrogen and lower fibrinogen levels in females. CT and BT maximum in blood group O due to more activation of von Willebrand’s Factor.